Unveiling the association between angiogenic imbalance in the gingival crevicular fluid in maternal periodontitis and spontaneous preterm birth - Albers, Daniela; Bendek, María José; Hernández, Marcela; Prieto, Diego; Rojas, Carolina; Mizgier, María Luisa; Hernández, Patricia; Illanes, Sebastián E.; Chaparro, Alejandra (Frontiers in Dental Medicine, 2025)
BackgroundEmerging evidence suggests that abnormal angiogenesis and imbalanced angiogenic factors may contribute to the development of spontaneous preterm birth (sPTB). In addition, pregnancy-related angiogenic changes and increased vascular permeability in periodontal tissues could amplify periodontal inflammation under hormonal influence.ObjectivesThis study aimed to evaluate the association between gingival crevicular fluid (GCF) levels of placental growth factor (PlGF) and soluble fms-like tyrosine kinase-1 (sFlt-1) and sPTB risk and to assess their correlation with periodontal disease severity during early pregnancy.Materials and methodsA prospective cohort study was conducted involving 348 pregnant women, with obstetric, clinical, and periodontal parameter assessments performed at 11–14 weeks of gestation, including probing depth (PD), clinical attachment loss (CAL), bleeding on probing (BOP), periodontal inflamed surface area (PISA), and plaque index score (PI). GCF samples were collected, and PlGF and sFlt-1 levels were measured using Magpix-Luminex® multiplex technology.ResultssPTB occurred in 3.45% (n = 12) of the participants. The women who had a sPTB had a significantly higher GCF PlGF/sFlt-1 ratio (p = 0.017) and lower sFlt-1 levels (p = 0.003) compared to those who had term pregnancies. A multivariate regression model combining the PlGF/sFlt-1 ratio, PI score, and first-trimester arterial blood pressure showed a predictive area under the curve of 0.78 (odds ratio 3.36, p = 0.008) for sPTB risk. Periodontal parameters, including PD sites >3 mm and PISA, were significantly worse in those with sPTB pregnancies (p = 0.032 and p = 0.047, respectively). Both PlGF and sFlt-1 levels were elevated in pregnant women with moderate to severe periodontitis compared to those with gingivitis or a healthy status (p < 0.0001), with significant positive correlations with inflammatory periodontal clinical parameters (p < 0.05).ConclusionAn early pregnancy imbalance of angiogenic and antiangiogenic factors in the GCF is associated with increased sPTB risk and greater periodontal inflammation. These findings suggest that angiogenic factors in the GCF may serve as promising non-invasive biomarkers for identifying women at elevated risk for sPTB.